Advocacy and Legislation for Regionalization Practices in the Treatment of Cardiogenic Shock: The Time Is Now - Kari Gorder; Steve Rudick; Timothy D Smith (US Cardiology Review)
Cardiogenic shock is a complex hemodynamic state that, despite improvements in care, often remains challenging to treat and confers a high mortality rate. Timely application of advanced strategies, including advanced hemodynamic management and mechanical circulatory support, is of the utmost importance for this critically ill patient population. Based on data and historic experiences with similar life-threatening conditions, a national system in the US of regionalized, structured care for patients with cardiogenic shock has the potential to improve outcomes and save lives. To enact this, national and state leaders, as well as federal regulatory bodies, physician thought leaders, industry representatives, and national organizations, must collaborate and advocate for a clear, structured cardiac shock center network with a tiered model for delivery of care for the sickest population of cardiac patients.